Analysis of the Arabic language book for the first intermediate grade in the light of knowledge economy skills (Journal of the College of Basic Education, 2023)
The current research aims to identify: the percentage of knowledge economy skills included in the Arabic language textbook for the first intermediate grade. Which helped prepare a list that included (7) seven main fields, and (40) forty sub-skills distributed over the fields of the knowledge economy as follows: (the knowledge field, the technological field, the communication field, the mental development field, the social field, the economic field, and the evaluation field). (Questionnaire) in its final form, with an agreement rate of (88%), and the researcher adopted the descriptive analytical approach, and he used statistical methods (statistical bag), and the Excel program to process the results of the research, and applied the following equations: the triple weighted mean, the Cooper equation, and the percentage weight, And the percentage, and the results of the research showed that the Arabic language books for the intermediate stage included the skills of knowledge economy in close proportions except for the skills of the economic field), where the skills of the technological field got ranked With a rate of (66%), the skills of the cognitive field ranked second with a rate of (62%), the skills of the field of assessment ranked third with a rate of (48%), and the skills of the field of mental development ranked fourth with a rate of (43%). Communication skills ranked fifth with a rate of (31%), social skills ranked sixth with a rate of (24%), and economic skills ranked seventh and last with a rate of (7%). Recommendations:1. The necessity of following up the authors of the Arabic language textbook for the first-grade stage in the percentages of including knowledge economy skills, and working to reconsider and achieve a balance in them.Suggestions:1. Conducting an analytical study of the Arabic language textbooks for the preparatory stage in the light of knowledge economy skills.